Awakening the leader within : - Cashman, Kevin (J. Wiley, 2003)
A spiritual journey that will take you to a new and inspiring understanding of leadership. Warren Bennis, Distinguished Professor of Business, USC and coauthor of Geeks and Geezers: How Era, Values and Defining Moments Shape Leaders. Awakening the Leader Within helps leaders to go beyond meeting their performance goals to achieving their life’s destiny. Don’t read this book if you are only concerned with your personal success. Read it if you are ready to begin the journey to a higher calling to really make a difference in the world.